Optimal planning of renewable energy-integrated electricity generation schemes with CO2 reduction target - Ab. Muis, Zarina (Elsevier B.V., 2010)
This paper presents a Mixed Integer Linear Programming (MILP) model that was developed for the optimalplanning of electricitygenerationschemes for a nation to meet a specified CO2 emission target. The model was developed and implemented in General Algebraic Modeling System (GAMS) for the fleet of electricitygeneration in Peninsular Malaysia. In order to reduce the CO2 emissions by 50% from current CO2 emission level, the optimizer selected a scheme which includes Integrated Gasification Combined Cycle (IGCC), Natural Gas Combined Cycle (NGCC), nuclear and biomass from landfill gas and palm oil residues. It was predicted that Malaysia has potential to generate up to nine percent of electricity from renewableenergy (RE) based on the available sources of RE in Malaysia.